Review of Approaches for Increasing Ophthalmic Bioavailability for Eye Drop Formulations - Lanier, Olivia L.; Manfre, Miranda G.; Bailey, Claire; Liu, Zhen; Sparks, Zachary; Kulkarni, Sandesh; Chauhan, Anuj (AAPS PharmSciTech, 2021)
Ophthalmic diseases represent a significant problem as over 2 billion people worldwide suffer from vison impairment and blindness. Eye drops account for around 90% of ophthalmic medications but are limited in success due to poor patient compliance and low bioavailability. Low bioavailability can be attributed to short retention times in the eye caused by rapid tear turnover and the difficulty of drug diffusion through the multi-layered structure of the eye that includes lipid-rich endothelial and epithelial layers as well as the stroma which is high in water content. In addition, there are barriers such as tight junctional complexes in the corneal epithelium, lacrimal turnover, nasolacrimal drainage, blinking reflexes, efflux transporters, drug metabolism by ocular enzymes, and drug binding to or repulsion from conjunctival mucins, tear proteins, and melanin. In order to maximize transport through the cornea while minimizing drug loss through other pathways, researchers have developed numerous methods to improve eye drop formulations including the addition of viscosity enhancers, permeability enhancers, mucoadhesives, and vasoconstrictors, or using formulations that include puncta occlusion, nanocarriers, or prodrugs. This review explains the mechanism behind each of these methods, examines their history, analyzes previous and current research, evaluates future applications, and discusses the pros and cons of each technique.